A flexible standalone system with integrated sensor feedback for multi-pad electrode FES of the hand - Loitz Jan C.; Reinert Aljoscha; Neumann Ann-Kristin; Quandt Fanny; Schroeder Dietmar; Krautschneider Wolfgang H. (Current Directions in Biomedical Engineering, 2016)
Functional electrical stimulation aims to help patients suffering from stroke or spinal cord injury to supplement lost motor function. Effective functional electrical stimulation requires precise placement of the stimulation electrode. Finding the correct placement, however, can be difficult and time consuming. Another common problem with functional electrical stimulation is early occurrence of muscle fatigue upon repetitive stimulation, limiting treatment efficiency. Both, precise electrode placement as well as the reduction of muscle fatigue can be achieved using multi-pad electrodes. Here we present a new standalone device for multi-pad functional electrical stimulation. The device is easy to use and designed to help patients recovering from stroke to train and perform opening of the hand.